SCAFFOLDING THROUGH GROUP DISCUSSIONS: ENHANCING EFL STUDENTS’ ORAL PROFICIENCY IN CHINESE UNIVERSITIES - Zhou , Yanyan; Wong , Alice Su Chu; Lee , Jocelyn Yee Vun3 (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This mixed-methods study examines how scaffolding strategies within group discussions affect the oral English proficiency of Chinese EFL undergraduates, addressing the conflict between exam-focused education and communicative competence in China. Based on Vygotsky’s Sociocultural Theory and Lave and Wenger’s Community of Practice, a 16-week intervention was conducted with 60 first-year non-English majors at Guilin University of Electronic Technology. The intervention combined cognitive, social, and technological scaffolding through role allocation, sentence frames, peer feedback, and technology-based reflection (WeChat and TikTok). Quantitative results from the Malaysian University English Test (MUET) speaking component showed significant improvement, with mean scores rising from Band 3.2 to 4.1 (p<0.001). Fluency and interactional competence improved by around 40%, while grammatical accuracy increased by 11%. Qualitative findings revealed greater willingness to communicate, lower anxiety, and stronger collaborative learning identities. Key success factors included phased scaffolding withdrawal, diverse grouping, and technology use. The study offers a tailored scaffolding model for Chinese EFL contexts and practical curriculum reform suggestions.